KEBUTUHAN DAN TANTANGAN AUDIT SYARIAH DAN AUDITOR SYARIAH - Peni Nugraheni (Faculty of Economics, Universitas Islam Indonesia, 2012)
Audited financial statement is the ways to make sure that information available on that report can be used to make decision, because there is an opinion of independent person (auditor) whether it presents a true and fair view of the company or not. Islamic bank established Shariah Supervisory Board (SSB) that one of its functions is to issue report about the compliance of Islamic bank in all activities with Islamic principles. This report is published with the external auditor’s annual report. Islamic bank is common to hire conventional auditor to audit its financial statements. However, because of the unique characteristics of Islamic bank, the using conventional auditor raises an issue whether it is adequate to audit and report on the accounts of an Islamic organization. By understanding the Islamic value, characteristics, activities, operation and normative content of Islamic banking report, this paper argues that conventional auditors is not adequate in both his knowledge and code of ethics, and therefore, the need for shariah audit become important for this institution. Shariah audit program, shariah audit qualification and education and independence of shariah auditor are the challenges to create qualified shariah auditors.